The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0103-84782008005000044
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding proteins of seminal plasma in Nellore bulls

Abstract: The aim of this study was to identify heparinbinding proteins (HBPs) In the last two decades there has been important progress in the identification and characterization of many components of seminal glands secretions, resulting in new perspectives regarding to the analysis of domestic animal ejaculated. Perhaps the most significant discovery has been the participation of heparin-binding proteins (HBPs) in the sperm capacitation (THÉRIEN et al., 1995). The spermatozoa are able to bind to heparin and also sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Further, the concentration of a 45 kDa protein was significantly (P<0.05) higher in bulls with average fertility than in their good and poor counterparts. Similar studies in seminal plasma of Nellore bulls (Fernandes et al 2009), rams (Martins et al 2013) and human (Kumar et al 2009) identified 8, 13 and 17 bands of affinity purified HBP with molecular weights ranging from 15 to 63 kDa, 10 to 232 kDa and 10 to 90 kDa, respectively. Further, Arangasamy et al (2005) and Kumar et al (2008) observed eight (11, 14, 18, 20, 31, 41, 65 and 71 kDa) and six (14, 20, 24, 31, 41 and 65 kDa) major HBP on SDS-PAGE in buffalo seminal plasma, respectively.…”
Section: Resultssupporting
confidence: 56%
“…Further, the concentration of a 45 kDa protein was significantly (P<0.05) higher in bulls with average fertility than in their good and poor counterparts. Similar studies in seminal plasma of Nellore bulls (Fernandes et al 2009), rams (Martins et al 2013) and human (Kumar et al 2009) identified 8, 13 and 17 bands of affinity purified HBP with molecular weights ranging from 15 to 63 kDa, 10 to 232 kDa and 10 to 90 kDa, respectively. Further, Arangasamy et al (2005) and Kumar et al (2008) observed eight (11, 14, 18, 20, 31, 41, 65 and 71 kDa) and six (14, 20, 24, 31, 41 and 65 kDa) major HBP on SDS-PAGE in buffalo seminal plasma, respectively.…”
Section: Resultssupporting
confidence: 56%
“…Another group of proteins investigated in the present study were heparin binding proteins. Until now, profiles of HBPs derived from seminal plasma and sperm membranes have been associated with bull fertility (Fernandes et al 2009). The majority of HBPs found in the YF of red deer were low-molecular weight proteins.…”
Section: Discussionmentioning
confidence: 99%
“…But, in the present study, proteins of 13, 17, 20, 25 showed an affinity for heparin. Electrophoretic analysis of affinity purified HBP fraction from SP of Nellore bulls (Fernandes et al, 2009), rams (Martin et al, 2013), buffalo bulls (Singh et al, 2014) and cross bred bulls (Cheema et al, 2016) revealed the presence of 8 (15 -63 kDa), 13 (10 -232 kDa), 8/6/9 (13 -71 kDa/14 -61 kDa/10 -170 kDa) and 14 (14-150 kDa) bands, respectively. Therefore, variation in number of HBP bands was also evident in other species.…”
Section: Characterization Of Seminal Plasma and Sperm Proteins By Sdsmentioning
confidence: 99%